Diyarbakır Çevresindeki Türkmen Alevileri Dedelerinden Eyüp Karkın'ın "Hızır İsen Kurtar Beni" İsimli Deyişinin Derlenmesi - Yalçın, Nihat (Journal of Alevism-Bektashism Studies, 2012)
in this article we discussed a religous poem (deyiş) of Eyüp Karkın, one of the disciples of the Dede Garkın community in Diyarbakır. The poem, which is (often) recited by the members of the Dede Garkın community in Diyarbakır, was equipped with a melody, while the narratives of the region Diyarbakır and Urfa were also considered. Thus the poem, which is known in Diyarbakır and Urfa and belongs to a popular poet (aşık) of the Dede Garkın community in Diyarbakır, was discussed for the first time in an article, and the method and techniques of compilation (derleme) were applied. For this purpose interviews, a field study, recordings and written documents were made use of. in the course of our research, we (also) concentrated on the works of the religious leaders (mürşit) of the Dede Garkın community in Diyarbakır, one of the turkmen-alevi communites in the region of Diyarbakır, because of their strong in.fiuence and activites in this region, which are still remembered. in general was the main subject of the article a piece of work of religious poems (deyiş) and its notation.
Keywords: Eyüb Karkın; Dede Garkın; Diyarbakır; Turkmen; deyiş [religious poem]; nefes [religious chanting]; Alevi